2019
DOI: 10.1038/s41467-019-09265-z
|View full text |Cite
|
Sign up to set email alerts
|

Stronger influence of anthropogenic disturbance than climate change on century-scale compositional changes in northern forests

Abstract: Predicting future ecosystem dynamics depends critically on an improved understanding of how disturbances and climate change have driven long-term ecological changes in the past. Here we assembled a dataset of >100,000 tree species lists from the 19th century across a broad region (>130,000km2) in temperate eastern Canada, as well as recent forest inventories, to test the effects of changes in anthropogenic disturbance, temperature and moisture on forest dynamics. We evaluate changes in forest composition using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 59 publications
(77 reference statements)
5
90
1
Order By: Relevance
“…This suggests that the pattern we uncovered might be caused primarily by an increase in abundance of species already present rather than by new colonization. Danneyrolles et al () also found that forest compositional changes over the last centuries (between 1790–1900 and 1980–2010) in deciduous forests of southern Québec were largely driven by changes in land use, favouring more disturbance‐adapted tree species, but did not find any signs of thermophilization. In contrast to our study, which covers a period of pronounced climate warming, Danneyrolles et al () investigated a period dominated by changes in land use and population, which might explain the absence of thermophilization signal in their results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This suggests that the pattern we uncovered might be caused primarily by an increase in abundance of species already present rather than by new colonization. Danneyrolles et al () also found that forest compositional changes over the last centuries (between 1790–1900 and 1980–2010) in deciduous forests of southern Québec were largely driven by changes in land use, favouring more disturbance‐adapted tree species, but did not find any signs of thermophilization. In contrast to our study, which covers a period of pronounced climate warming, Danneyrolles et al () investigated a period dominated by changes in land use and population, which might explain the absence of thermophilization signal in their results.…”
Section: Discussionmentioning
confidence: 98%
“…Danneyrolles et al () also found that forest compositional changes over the last centuries (between 1790–1900 and 1980–2010) in deciduous forests of southern Québec were largely driven by changes in land use, favouring more disturbance‐adapted tree species, but did not find any signs of thermophilization. In contrast to our study, which covers a period of pronounced climate warming, Danneyrolles et al () investigated a period dominated by changes in land use and population, which might explain the absence of thermophilization signal in their results. In light of their results, we hypothesize that some of the thermophilization we reported here in the sugar maple domains is, in fact, the result of secondary succession after historical disturbances.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1). Since the changes experienced by the field layer are further buffered by the canopy layer (De Frenne et al, 2019;Lembrechts et al, 2020) , and both canopies and understories have been shown to have small responses to climate change compared to land-use at decadal timescales (Danneyrolles et al, 2019;Tonteri et al, 2016) , the direct effect of climate change was left out of the models.…”
Section: Environmental Changesmentioning
confidence: 99%